THE USE DIGITAL SERVICES AND PRODUCT COMPLETENESS TO MAKE IT EASIER FOR GENERATION Z TO CHOOSE SAVINGS AT ISLAMIC BANKS - Trimulato; Ahmad Rodoni; Erika Amelia (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyse the impact of digital services, product completeness, and promotional activities on the decision of Gen Z to choose savings in Islamic banks, with a focus on the moderating role of promotions. The research employed a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to evaluate the relationships between the variables. Data were collected through a survey of Gen Z respondents who are potential customers of Islamic banks. The findings reveal that digital services have a significant direct impact on the decision of Gen Z, while product completeness shows a weaker direct influence. However, when moderated by promotional activities, both digital services and product completeness have a stronger indirect effect on the decision to choose savings in Islamic banks. The study concludes that Islamic banks should enhance their digital services and carefully design promotional strategies to effectively attract Gen Z customers. Product completeness, although less significant on its own, plays a crucial role when coupled with effective promotions. This study contributes to the literature on Islamic banking by examining the role of digital services, product completeness, and promotion in influencing Generation Z’s decision to choose Islamic bank savings. The study highlights the moderating role of promotion in strengthening the relationship between digital services and Gen Z decision-making. The findings provide practical insights for Islamic banks to develop digital-based services and targeted promotional strategies to attract young customers.